2007
DOI: 10.1016/j.mbs.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Bringing consistency to simulation of population models – Poisson Simulation as a bridge between micro and macro simulation

Abstract: Population models concern collections of discrete entities such as atoms, cells, humans, animals, etc., where the focus is on the number of entities in a population. Because of the complexity of such models, simulation is usually needed to reproduce their complete dynamic and stochastic behaviour. Two main types of simulation models are used for different purposes, namely micro-simulation models, where each individual is described with its particular attributes and behaviour, and macro-simulation models based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Stochastic simulations of the generalized-growth model were generated through a Poisson simulation approach [11]. To assess the impact of assuming exponential growth in the context of near-exponential growth dynamics, we estimated the growth rate “ r ” for the exponential growth model for each of the 500 stochastic realizations to generate a distribution of the estimates of the growth rate “ r ”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stochastic simulations of the generalized-growth model were generated through a Poisson simulation approach [11]. To assess the impact of assuming exponential growth in the context of near-exponential growth dynamics, we estimated the growth rate “ r ” for the exponential growth model for each of the 500 stochastic realizations to generate a distribution of the estimates of the growth rate “ r ”.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 500 stochastic simulations were generated through a Poisson simulation approach [11]. The gray curves correspond to the ensemble of stochastic simulations.…”
Section: Figurementioning
confidence: 99%
“…It also revealed a simple and direct relationship between discrete and continuous compartment models. Gustafsson and Sternad [23], based on [14], showed that agent-and entity-based and compartment-based models will produce fully consistent results if a number of simple rules are obeyed. In [24] this was extended to include situation-based models.…”
Section: Discussionmentioning
confidence: 99%
“…A brief presentation of stochastic compartment-based modelling using the Poisson Simulation approach is given in Appendix B. See also [23]. Constructions like queues of different kinds can easily be accomplished within compartment-based modelling by using Poisson Simulation, see [14].…”
Section: Time Handling Strategiesmentioning
confidence: 99%
“…It has an advantage over the chain binomial models in the dynamic modeling of infectious disease spread. In the chain binomial models, varying the selection of can distort the dynamic patterns [31]. In contrast, the Poisson distribution can be freely adjusted with respect to without affecting the stochastic process due to the Poisson property.…”
Section: Methodsmentioning
confidence: 99%